Local culture and resistance to shocks in economic forecasts: a case study of Greece - Tubadji, Annie; Angelis, Vassilis; Nijkamp, Peter (Economics and Business Letters, 2014)
This paper offers an analysis of errors in stochastic forecasts in case of economic shocks, on the basis of local intangible investments and historic cultural persistence in Greece. The main objective of the paper is to demonstrate that local culture is a factor of significance for resistance to economic shocks. To operationalize our study, we use two data sources: (i) the European University Institute (EUI) European Regional Dataset (ERD) which offers a time-series for Greece on a NUTS-III level for the period from 1980 till 2011, containing information about total employment, sectoral employment (where intangible investment related sectors are captured in the analysis), and gross value added; (ii) the Hellenic Ministry of Culture Permanent List of Designated Archaeological Sites and Monuments in Greece. We analyze the relationship between the residuals (differences of prediction and real value) with sectoral specialization and cultural milieu. We find evidence for a Tieboutian (local culture and local intangible investment related) foundation for the resistance to economic shocks in Greece in the period 2008 - 2011.